Experimental system for the optimization of the parallel manipulator control - Vinh, Nguyen Xuan; Ha, Le Quoc; Lam, Nguyen Ngoc; Quoc, Le Hoai; Thanh, Nguyen Minh (Journal of Computer Science and Cybernetics, 2015)
This paper presents the results of an experimental system design for the optimization of parallel manipulator control based on an optimal configuration. The experimental system is an open design for various different configurations and controllers to support parallel manipulator research and applications. Traditional PID control and self-tuning fuzzy PID control algorithm are applied for motion control of parallel manipulator. The quality system standard will be analyzed and compared with simulation results. The system can be a useful tool for research and training.